Evaluation of flagellum-related proteins FliD and FspA as subunit vaccines against Campylobacter jejuni colonisation in chickens. Issue 15 (4th April 2016) - Chintoan-Uta, C.; Cassady-Cain, R.L.; Stevens, M.P.
Abstract: Campylobacter is the leading cause of food-borne diarrhoea in humans in the developed world and consumption of contaminated poultry meat is the main source of infection. Vaccination of broilers could reduce carcass contamination and zoonotic infections. Towards this aim, we evaluated recombinant anti- Campylobacter subunit vaccines based on the flagellum-capping protein FliD and the flagellum-secreted protein FspA as they are immunogenic in chickens and the flagellum is vital for colonisation. In three studies, a recombinant FliD vaccine induced a transient but reproducible and statistically significant decrease of c. 2 log10  CFU/g in caecal colonisation levels at 49 days post-primary vaccination on the day of hatch. Levels of serum IgY specific to FliD positively correlated with caecal bacterial counts in individual birds, indicating that such antibodies may not play a role in protection. The data add to the limited repertoire of candidate antigens for the control of a key foodborne zoonosis.